Critique of the Hadith of Fadail Al-Sham in Relation to the Dynamics of the Palestine-Israel Conflict - Satedy, Andri Lupias; Najib, Moh.; Wibisono, M. Yusuf; Mulyana, Mulyana (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study critically examines hadiths on Fadail al-Sham (virtues of the Levant) and their relevance to the Palestine-Israel conflict, framed historically from the 1936 Arab Revolt through Gaza conflicts (2008–2024). Intertwined political, territorial, identity, and religious factors have fueled escalations, casualties, displacement, and destruction. Employing takhrij and dirasah al-asanid, alongside interdisciplinary hadith criticism and conflict resolution studies, the research assesses sanad/matn authenticity, historical interpretations, conflict dynamics, and prophetic contributions to peacebuilding. The objectives are: Evaluate hadith quality; trace interpretive evolution; analyze conflict relevance; propose sustainable resolutions. Findings reveal 18 authentic/hasan hadiths, dominated by Shami narrations with reinforcing shawahid. Thematically categorized as: Bait al-Maqdis sanctity, Divine protection of Sham, eschatology, and Muslim steadfastness. These affirm Fadail al-Sham as core mu'tabar hadith, informing religious dimensions of the conflict.